Understanding the genome architecture and evolution of Shiga toxin encoding bacteriophages of Escherichia coli - Pinto, Graça (2021)
Shiga toxin-producing Escherichia coli (STEC) is an important foodborne pathogen, and its major virulence factor is their ability to produce Shiga toxins. This toxin is coded by the stx gene, acquired through the insertion of a prophage into their genome. In our study, 179 STEC genomes were analysed for their serotype, distribution, and stx gene variants. Stx phages were also analysed and grouped based on shared gene content. We show that most STEC were isolated from different sources and geographical regions and belong to the non-O157 serotypes (73%). While the majority of STEC encode a single stx gene (61%), strains coding for two (35%), three (3%) and four (1%) stx genes were also found, being stx2a the most prevalent gene variant. PHASTER analysis found stx genes in intact prophage regions, indicating they are phage-borne. Stx phages from our dataset were grouped into four clusters (A, B, C and D), three subclusters (A1, A2 and A3) and one singleton, in agreement with the predicted virion morphologies. Stx phage genomes are highly diverse with a vast number of 1,838 gene phamilies (phams) of related sequences (of which 677 are orphams i.e. unique genes) and although having high mosaicism, they are generally organized into three major transcripts (structural, metabolism, lysis and virulence). There is a strong selective pressure to maintain the stx genes location in close proximity to the lytic cassette composed of predicted SAR-endolysin and pin-holin lytic proteins. Taken together, we demonstrate that Stx phages genomes are highly diverse, with several lysislysogeny regulatory systems identified but with a conserved lytic system always adjacent to stx genes.